Intelligent support model for flood victims - Che Pa, Noraziah; Ab. Aziz, Azizi; Aulia, Vera; Abu Bakar, Juliana Aida (2015)
Stress is a common psychological stimulus that occurs in a person caused by stressors.Natural disaster is a specific form of stressor that can carry wide area of implications in the population. It is the most common factors which contribute to high level of stress and other psychological problems of individuals.Therefore, intervention must be introduced to help victims who have stress during natural disasters.In order to provide an effective intervention for victims in an evacuation center, a supporting software agent could be helpful. Focusing on providing support to flood victims, this paper presents a development of an intelligent support model of victims' stress in flood disaster based on the existing computational model.The research methodology deploys four phases; identification of properties, formalization, simulation, and performance evaluation.The computational support model is tested by using simulation in two different conditions; person without therapy and person following the therapy intervention.Results suggest that the resilience level is high due to person’s capability of enhancing one’s problem focus coping skills rather than relying on emotional focus coping skills.